2020
DOI: 10.1088/1361-6382/ab77ec
|View full text |Cite
|
Sign up to set email alerts
|

Joule–Thomson expansion of a specific black hole in f(R) gravity coupled with Yang–Mills field

Abstract: In this paper, we study the Joule–Thomson expansion of a specific black hole in f(R) gravity coupled with Yang–Mills field. Firstly, four-dimensional equation of state and the Joule–Thomson coefficient are derived from thermodynamic quantities, the critical temperature and the inversion temperature are obtained, and the isenthalpic curves and the inversion curves are plotted in the T − P plane. Then, by considering the higher dimensions black hole, the inversion temperature is obtained, the isenthalpic curves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 60 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…The Joule-Thomson expansion of black holes was investigated in [37] for the first time, then this subject was comprehensively studied in the literature [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. The inversion curves that separate heating-cooling regions in T − P plane for isenthalpic curves with different parameters are present.…”
Section: Introductionmentioning
confidence: 99%
“…The Joule-Thomson expansion of black holes was investigated in [37] for the first time, then this subject was comprehensively studied in the literature [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. The inversion curves that separate heating-cooling regions in T − P plane for isenthalpic curves with different parameters are present.…”
Section: Introductionmentioning
confidence: 99%
“…[ 46 ] These works indicated that, different from the van der Waals‐like fluid, the black hole in the AdS space has only a minimum inversion temperature, without a maximum one. The successive studies in various extended theories of gravity further confirmed these conclusions, [ 47–84 ] and the basic reason is the slight difference between the EoS of the black hole and the van der Waals‐like fluid.…”
Section: Introductionmentioning
confidence: 75%
“…The BH as a thermodynamic system is similar to the classical thermodynamic systems. For the BHs in AdS spacetime, the charged AdS BHs are almost equivalent to the van der Waals (vdW) liquid-gas system [13][14][15][16][17][18]. The BH is not only regarded as a thermodynamic system but also as a strong gravitational one.…”
Section: Introductionmentioning
confidence: 99%